Endovascular Neuromodulation: Safety Profile and Future Directions - Raza, Samad A.; Opie, Nicholas L.; Morokoff, Andrew; Sharma, Rahul P.; Mitchell, Peter J.; Oxley, Thomas J. (Frontiers in Neurology, 2020)
Endovascular neuromodulation is an emerging technology that represents a synthesis between interventional neurology and neural engineering. The prototypical endovascular neural interface is the StentrodeTM, a stent-electrode array which can be implanted into the superior sagittal sinus via percutaneous catheter venography, and transmits signals through a transvenous lead to a receiver located subcutaneously in the chest. Whilst the StentrodeTM has been conceptually validated in ovine models, questions remain about the long term viability and safety of this device in human recipients. Although technical precedence for venous sinus stenting already exists in the setting of idiopathic intracranial hypertension, long term implantation of a lead within the intracranial veins has never been previously achieved. Contrastingly, transvenous leads have been successfully employed for decades in the setting of implantable cardiac pacemakers and defibrillators. In the current absence of human data on the StentrodeTM, the literature on these structurally comparable devices provides valuable lessons that can be translated to the setting of endovascular neuromodulation. This review will explore this literature in order to understand the potential risks of the StentrodeTM and define avenues where further research and development are necessary in order to optimize this device for human application.